Association between respiratory syncytial viral disease and the subsequent risk of the first episode of severe asthma in different subgroups of high-risk Australian children: a whole-of-population-based cohort study. Issue 11 (8th November 2017) - Homaira, Nusrat; Briggs, Nancy; Pardy, Christopher; Hanly, Mark; Oei, Ju-Lee; Hilder, Lisa; Bajuk, Barbara; Lui, Kei; Rawlinson, William; Snelling, Tom; Jaffe, Adam
Abstract : Objective: To determine the contribution of respiratory syncytial virus (RSV) to the subsequent development of severe asthma in different subgroups of children at risk of severe RSV disease. Settings: The study was conducted in New South Wales (NSW), Australia. Participants: The study comprised all children born in NSW between 2000 and 2010 with complete follow-up till 31 December 2011. The cohort was divided into three subgroups: (1) non-Indigenous high-risk children: non-Indigenous children born preterm or born with a low birth weight; (2) Indigenous children: children of mothers whose Indigenous status was recorded as Aboriginal and/or Torres Strait Islander and (3) non-Indigenous standard risk children: all other non-Indigenous term children. Primary outcome measure: Risk of development of severe asthma in different subgroups of children who had RSV hospitalisation in the first 2 years of life compared with those who did not. Design: We performed a retrospective cohort analysis using population-based linked administrative data. Extended Cox model was used to determine HR and 95% CI around the HR for first asthma hospitalisation in different subgroups of children. Results: The cohort comprised 847 516 children born between 2000 and 2010. In the adjusted Cox model, the HR of first asthma hospitalisation was higher and comparable across all subgroups of children who had RSV hospitalisation compared with those who did not. The HR (95% CI) was highest in children aged 2–3 years; 4.3 (95% CI 3.8 to 4.9) for high-risk, 4.0 (95% CI 3.3 to 4.8) for Indigenous and 3.9 (95% CI 3.7 to 4.1) for non-Indigenous standard risk children. This risk persisted beyond 7 years of age. Conclusion: This large study confirms a comparable increased risk of first asthma hospitalisation following RSV disease in the first 2 years of life across different subgroups children at risk.